Humble women, powerful nuns : a female struggle for autonomy in a men's church - Suenens, Kristien, 1981- (Leuven : Leuven university press, 2020)
Nineteenth-century female congregation founders could achieve levels of autonomy, power and prestige that were beyond reach for most women of their time. With a subject hidden for a long time behind a curtain of modesty and mystery, this book recounts the fascinating but ambiguous life stories of four Belgian religious women. A close reading of their personal writings unveils their conflicted existence: ambitious, engaged and bold on the one hand, suffering and isolated on the other, they were both victims and promotors of a nineteenth-century ideal of female submission. As religious and social entrepreneurs these women played an influential role in the revival of the church and the development of education, health care and social provisions in modern Belgium. But, equally well, they were bound to rigid gender patterns and adherents of an ultramontane church ideology that fundamentally distrusted modern society.
Keywords: Cornet, Antoinette, -- 1820-1886.; Kestre, Fanny, -- 1824-1882; Meeûs, Anna de, -- 1823-1904.; Telghuis, Wilhelmina, -- 1824-1907.; 1800-1899.; Catholic women; Monastic and religious life of women; Monasticism and religious orders for women; Nuns; Religion; Superiors, Religious; Women in the Catholic Church; Belgium; Biographies; History